Upaya Meningkatkan Hasil Belajar Kognitif Peserta Didik melalui Model Problem Based Learning (PBL) - Cahyani, Regina Atikoh; Putri, Rahmah Evita; Yenira, Fitria (TSAQOFAH, 2025)
This study aims to improve the cognitive learning outcomes of Class IX.3 students at SMP Negeri 10 Padang through the implementation of the Problem Based Learning (PBL) model in the science subject (Ilmu Pengetahuan Alam/IPA). The research employed a Classroom Action Research (Penelitian Tindakan Kelas) method conducted over two cycles, each consisting of planning, action implementation, observation, and reflection stages. Data were collected through observations of learning activities and evaluations of student achievement, then analyzed quantitatively to measure improvements in student performance. The results showed a significant increase in the class average score, from 64.59 in Cycle I to 70.00 in Cycle II, along with an improvement in mastery learning percentage from 21.88% to 59.38%. Additionally, the application of the PBL model enhanced active student engagement during the learning process, as reflected in increased participation in asking questions, engaging in discussions, and solving problems collaboratively. These findings demonstrate that the PBL model is effective not only in improving cognitive learning outcomes but also in enhancing the quality of classroom interaction. Therefore, PBL can be considered a relevant alternative instructional strategy to strengthen students’ conceptual understanding and critical thinking skills in science learning.